A comparison of food safety conformity between cattle and pig slaughterhouses. (October 2022) - Jakubowska-Gawlik, Katarzyna; Kolanowski, Wojciech; Murali, Aparna P.; Trafialek, Joanna
Abstract: The aim of the study was to evaluate and compare the level of conformity with food safety requirements in cattle and pig slaughterhouses in the qualification procedure of beef and pork suppliers to a large-scale meat processing plant. Seventy-two slaughterhouses supplying beef and pork to the meat processing plant were audited. The audits were carried out in 2019–2020 during the COVID-19 pandemic. Most of the evaluated slaughterhouses met the audit requirements, but 10% were not qualified. There were two and half times more disqualified pig slaughterhouses than cattle ones. Large-sized slaughterhouses were scored significantly better than the medium-sized ones. The results made it possible to identify areas requiring urgent improvement in slaughterhouses, especially in the case of food safety/HACCP and non-conformities control, site hygiene, and pest control. Significantly more complete fulfillment of the requirements was found in cattle than in pig slaughterhouses. The highest differences between cattle and pig slaughterhouses were found in the area of site hygiene, pest control, and production process criteria. The highest scored criterion for both types of slaughterhouse was SARS-CoV-2/COVID-19 issues. This indicates that prevention spreading of COVID-19 in the work environment was highly ensured.